Goods and services tax (GST) in India: Prospect for states - Mohd. Azam Khan; Nagma Shadab (Budgetary Research Review (BRR), 2012)
Goods and services tax (GST) is a broad based and a single comprehensive tax levied at every stage of the production and distribution chain with applicable set-off in respect of the tax remitted at previous stages. It is basically a tax on final consumption integrates the union excise duties, custom duties, services tax and state VAT. Presently around 140 countries have adopted the GST pattern, including India. The GST would be beneficial for the consumers as it reduces the final burden of taxation. For Government it leads the reduction of tax compliance efforts and administrative costs and for business units it leads transparency, complete set-off and removal of cascading effect of taxation. It is in this background that the present paper tries to explain the significance of GST in India and its prospects for states to generate revenue and ensure transparency in tax structure. This paper is organized into seven sections. Section two presents justification for dual structure of GST in India. The third part presents the rate structure under GST work in India. The fourth segment is concerned with the working of GST in India. The fifth part shows the international experiences of GST at state level in India. The seventh and final part is related to conclusion and policy recommendations.
Keywords: H2; H71; 330; Goods and service tax; budgetary revenues; India